2007
DOI: 10.3354/meps06978
|View full text |Cite
|
Sign up to set email alerts
|

Linking behavioural ecology and oceanography: larval behaviour determines growth, mortality and dispersal

Abstract: Highly resolved general circulation models (GCMs) now generate realistic flow fields, and have revealed how sensitive larval drift routes are to vertical positioning in the water column. Sensible representation of behavioural processes then becomes essential to generate reliable patterns of environmental exposure (growth and survival), larval drift trajectories and dispersal. Existing individual-based models involving larval fish allow individuals to vary only in their attributes such as spatial coordinates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
142
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 59 publications
(65 reference statements)
1
142
0
1
Order By: Relevance
“…It has been shown that fish can detect fine-scale stimuli induced by the current and actively react to them from early larval stages onwards (Garner 1999;Stoll and Beeck 2012). In marine fish ecology, the importance of larval behaviour for dispersal has been recognized during the past decade (Fiksen et al 2007;Gallego et al 2007;Leis 2007), and the need to break "the behavioural black box" has been realized (Pineda et al 2007). Moreover, basic behavioural features of fish larvae have already been successfully incorporated into elaborate 3D models of physical-biological interactions, which have increasingly become an integral tool for understanding larval fish dynamics in the sea (Gallego et al 2007), while in rivers these methods are in their infancy (Schludermann et al 2012;Lechner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that fish can detect fine-scale stimuli induced by the current and actively react to them from early larval stages onwards (Garner 1999;Stoll and Beeck 2012). In marine fish ecology, the importance of larval behaviour for dispersal has been recognized during the past decade (Fiksen et al 2007;Gallego et al 2007;Leis 2007), and the need to break "the behavioural black box" has been realized (Pineda et al 2007). Moreover, basic behavioural features of fish larvae have already been successfully incorporated into elaborate 3D models of physical-biological interactions, which have increasingly become an integral tool for understanding larval fish dynamics in the sea (Gallego et al 2007), while in rivers these methods are in their infancy (Schludermann et al 2012;Lechner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fiksen et al (2007) stated that larval fish simply execute genetically preprogrammed responses to internal states or external stimuli. From our analysis, it could not be ultimately clarified whether the observed higher survival probability of larval sprat during the past decade was due to a change in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Wieland and Zuzarte (1991) found a deep maximum of small larvae (, 6 mm) occurring at 70-75 m and older larvae (up to 19 mm) predominantly in the upper 45 m. These differences in the vertical distribution of larvae with ontogeny suggest that most larvae hatch at deeper layers and then migrate to the upper layers, where they remain until at least the juvenile phase (Voss et al 2007). Besides ontogenetic changes in depth preference, vertical positions chosen by larval fish may be due to behavioral response to environmental gradients (Vikebø et al 2007). Strong selection pressures on habitat selection in larval sprat could be expected since the pelagic environment in the Baltic Sea is characterized by strong vertical gradients of abiotic as well as biotic variables that affect the growth of sprat larvae (i.e., temperature, prey concentrations, and the probability of being advected into unfavorable areas for Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations